2013
DOI: 10.1007/s00192-013-2055-5
|View full text |Cite
|
Sign up to set email alerts
|

Female urethral dilation

Abstract: Conflicting results and diverse opinions have characterized the use of UD until present time. Professional societies are urged to attend to this issue, and to identify possible areas where UD could be potentially investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…This, despite a lack of scientific evidence supporting the long-term efficacy. There have been a handful of randomized controlled trials of varying strengths evaluating the success of urethral dilation, but none of these addressed FUSD specifically [ 16 ]. Instead, they were targeting recurrent urinary tract infections or non-specific lower urinary tract symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…This, despite a lack of scientific evidence supporting the long-term efficacy. There have been a handful of randomized controlled trials of varying strengths evaluating the success of urethral dilation, but none of these addressed FUSD specifically [ 16 ]. Instead, they were targeting recurrent urinary tract infections or non-specific lower urinary tract symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…It should be considered that there is a potential variant of this entity, of an acquired nature, in which fibrosis or stenosis forms secondary to repeated urinary tract infections in young girls. 5 Although the clinical management may be similar, these are 2 distinct entities and should be considered as such (eg, when further studies are indicated).…”
Section: Discussionmentioning
confidence: 99%
“…In 2013, Bazi and co-workers supported Yoon’s statement and suggested that there is no justification for urethral dilation for the treatment of UPS, and that this procedure may do more harm than good. Urethral dilation is an invasive surgical procedure that causes irritative symptoms and is associated with various complications, including infections, incontinence and stricture development [16].…”
Section: Discussionmentioning
confidence: 99%
“…Many different treatment methods, including local corticosteroids, antibiotics, alpha-blockers, topical vaginal estrogen, female urethral dilation, local anesthetics, mucosal protecting agents, acupuncture, antidepressants, bladder training, and physical therapy, have been tested with various effects [5, 10, 1316]. In previous studies, it is recommended that the therapeutic approach should be multimodal, and it is stated that “treatment at its best is by trial and error” [6, 10, 13].…”
Section: Introductionmentioning
confidence: 99%